5PSQ-049 Atezolizumab: efficacy and safety in advanced non-small cell lung cancer. (March 2019) - Fernandez, D; Otero, C; Álamo, A; Mateos, E; Lombardero, M; Lujan, ME; Dorta, D; Dominguez, A
Abstract : Background: Results of the OAK study demonstrated that atezolizumab improved median overall survival and progression-free survival of patients with advanced non-small cell lung cancer (NSCLC). Purpose: Evaluate the efficacy and safety of atezolizumab treatment in patients with metastasic or advanced NSCLC in second and successive lines. Material and methods: Retrospective observational study in which patients with NSCLC were included who started treatment with atezolizumab in the second or successive line, during the period from April to September 2018. Data were collected on demographic variables (age and sex) and clinical variables (ECOG, smoking habit, previous chemotherapy, dose, number of cycles and adverse reactions) through clinical history (Selene) and the oncological prescription program (Farmatools). The descriptive statistical analysis was carried out through the SPSS vs22.0 program. Efficacy was evaluated in terms of progression-free survival (PFS) and overall survival (OS), calculated by the Kaplan–Meier method. To assess safety, the severity of adverse events (AA) was measured according to CTCAEv4.0 Results: We analysed 14 patients, 9 males and 5 females. Ninety-three per cent were smokers or ex-smokers, and 7% had never smoked. Eleven patients had ECOG 0–1 and three ECOG 2% and 93% had metastases at the start of treatment with atezolizumab. All patients had received prior platinum-based chemotherapy as first-line treatment. The dose administered was 1200 mg every 3 weeks and the average of cycles was four. The median of PFS was 4.8 months (95% CI: 1.0 to 8.6) and the average of OS 4.5 months (95% CI: 3.6 to 5.4). 57.14% of the patients presented some AA of any degree and only 12.5% were grade 3–4. The most frequent were renal failure (37.5%), diarrhoea (25%), rash (25%), hypersensitivity (12.5%), thrombocytopaenia (12.5%), lung infection (12.5%), oedema (12.5%), emésis (12.5%) and decreased appetite (12.5%) Conclusion: The efficacy in terms of OS obtained was lower than that of the OAK study (13.8 months). However, when the PFS was analysed in our study, it was superior to that of the OAK study (PFS 2.8 months). In general, atezolizumab presents an acceptable safety profile, the most frequent AEs coincide with those described in the literature. References and/or acknowledgements: No conflict of interest.